KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP DI KAMPUNG CIBOGO PADA MATERI SPLDV - Anggun Budi Lestari; Ekasatya Aldila Afriansyah (Universitas Muhammadiyah Makassar, 2021)
Problem-solving is one of the skills that must be possessed by every student, especially in learning mathematics. By having problem-solving skills, students can solve every problem well in every field. The results of previous studies show that the ability to solve mathematical problems is still low, especially in the SPLDV material. This study aims to determine the mathematical problem-solving ability of junior high school students on the SPLDV material. This research is qualitative research, with the research sample is junior high school students in Cibogo village. Sampling was done randomly and randomly selected four students. The data collection techniques used were observation, tests, and interviews, while the data analysis techniques used data reduction, data presentation, and conclusion drawing/verification. The results showed that students' mathematical problem-solving abilities were still low, seen from the percentage of the results of the analysis of students' mathematical problem-solving abilities, namely the percentage of the first indicator, namely identifying the known elements, which were asked and the adequacy of the required elements, the percentage of the first sub was 100%. While in the second sub, the percentage is 0%. Furthermore, in the second indicator, namely formulating mathematical problems or compiling mathematical models, the first sub percentage is 75% the same as the second sub the percentage is 75%. Then on the third indicator, namely choosing and setting strategies to solve problems inside or outside mathematics, the first sub percentage is 0%, as well as the second sub percentage, is 0%. And in the fourth indicator, namely explaining or interpreting the results according to the original problem and checking the correctness of the results or answers, the first sub percentage is 25%, and in the second sub, the percentage is 25%.